Shifts from specialised to generalised pollination systems in Miconieae (Melastomataceae) and their relation with anther morphology and seed number. (11th February 2016) - Brito, V. L. G.; Fendrich, T. G.; Smidt, E. C.; Varassin, I. G.; Goldenberg, R.
Abstract: Most species in Melastomataceae have poricidal anthers related to specialised bee buzz‐pollination, while some have anthers with large openings associated to non‐bee pollination systems. We tracked the evolution of anther morphology and seed number on the Miconieae phylogenetic tree to understand the evolutionary shifts in such pollination systems. Anther morphometric data and seed number were recorded for 54 taxa. Pollinators (bees, flies, wasps) were recorded for 20 available species. Ancestral state reconstruction was made using Maximum Likelihood from nrITS sequences. We used phylogenetic eigenvector regressions to estimate phylogenetic signal and the adaptive component for these traits. Species pollinated by bees or bees and wasps tend to have smaller pores and fruits with more seeds. Species pollinated by flies or flies and bees and/or wasps tend to have larger pores and fruits with less seeds. Independent evolution occurred three times for anthers with large pores and twice for fruits with few seeds. We detected a phylogenetic signal in both traits, and negative correlated evolution between them. In actinomorphic small‐flowered Miconieae, changes in anther morphology can be related to generalisation in the pollination system incorporating flies and wasps as pollinators and lessening the importance of buzzing bees in such process. Differences in pollen removal and deposition may explain differences in anther morphology and seed number in Miconieae.